Effect of geometrical contraction on vortex breakdown of swirling turbulent flow in a model combustor. (15th April 2016) - Wu, Y.; Carlsson, C.; Szasz, R.; Peng, L.; Fuchs, L.; Bai, X.S.
Abstract: Large Eddy Simulation (LES) studies of isothermal and incompressible turbulent swirling flows in a model gas turbine combustion chamber geometry have been carried out. The focus is on the effect of outlet geometry contraction on the vortex breakdown structure and the precessing vortex core in the chamber. Nine different outlet geometries with different contraction ratio C r are considered. The results from a baseline case are compared with experimental data in the literature. The swirling flow is generated using a swirler with fifteen guide vanes similar to an existing industrial gas turbine burner. In all cases the swirler and the main chamber geometry are kept the same. The detailed swirler geometry is considered in the simulation using unstructured grids. Sensitivity tests on the influence of the grid resolution and the subgrid scale models are carried out. The mean flow field shows different vortex breakdown structures when the contraction ratio changes from 0.325 to 1.0. In particular, along the axis of the chamber the flow is shown to switch its direction when the contraction increases as a result of the change of the structure of the center recirculation zone. The underlying flow physics is analyzed by comparing the budget terms in the momentum equations, and by performing a global instability analysis.